2023
DOI: 10.1021/acs.nanolett.3c02555
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Modulation of Polarized Thermal Radiation from an On-Chip Aligned Carbon Nanotube Film

Shinichiro Matano,
Natsumi Komatsu,
Yui Shimura
et al.

Abstract: Spectroscopic analysis with polarized light has been widely used to investigate molecular structure and material behavior. A broadband polarized light source that can be switched on and off at a high speed is indispensable for reading faint signals, but such a source has not been developed. Here, using aligned carbon nanotube (CNT) films, we have developed broadband thermal emitters of polarized infrared radiation with switching speeds of ≲20 MHz. We found that the switching speed depends on whether the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The suspended devices present relaxation time values of about a few microseconds (5.7 μs parallel, 9.7 μs perpendicular), while the on-substrate devices have a relaxation time value of about hundreds of nanoseconds (0.11 μs parallel, 0.17 μs perpendicular). As explained in our previous work (ref 25), the parallel configurations show a faster response speed rather than the perpendicular ones in both suspended and onsubstrate structures because of the larger thermal conductivity along the channel direction that leads to faster thermal transport. However, the response speeds of the suspended structures are 1 order of magnitude larger than the respective on-substrate ones.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The suspended devices present relaxation time values of about a few microseconds (5.7 μs parallel, 9.7 μs perpendicular), while the on-substrate devices have a relaxation time value of about hundreds of nanoseconds (0.11 μs parallel, 0.17 μs perpendicular). As explained in our previous work (ref 25), the parallel configurations show a faster response speed rather than the perpendicular ones in both suspended and onsubstrate structures because of the larger thermal conductivity along the channel direction that leads to faster thermal transport. However, the response speeds of the suspended structures are 1 order of magnitude larger than the respective on-substrate ones.…”
Section: Resultsmentioning
confidence: 68%
“…Radiation sources based on nanocarbon materials, such as graphene and carbon nanotubes (CNTs), have emerged as a promising solution for achieving micro/nano-scale emitters of broadband polarized radiation, particularly thermal radiation. Previous research has explored the thermal emission characteristics of CNTs in various configurations, including bundled ropes, vertically aligned arrays, and individual wires. Notably, Matano et al , have reported polarized thermal radiation emitted from a film of highly aligned CNTs on a SiO 2 /Si substrate. However, the achieved polarization degree remained unsatisfactory for practical applications, although CNTs have the potential to emit highly polarized radiation. In the previous study, the degree of light polarization (DLP), defined as D L P = I I I + I (where I ∥ and I ⊥ are the intensities of light polarized in the parallel and perpendicular direction, respectively), was limited to ∼0.6, and the thermal performance of the devices was poor due to the presence of the underlying oxide layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation